Penetapan Status Anak Akibat Perkawinan Dibawah Tangan: (Studi pada Perkara Nomor 77/pdt.p/2020/PA.Gtlo) - Rahmawati Rahman; Muh. Tamrin (Universitas Serang Raya, 2021)
The purpose of this study is to find out the legal position of the status of children born due to marriage under the hands and to find out the legal considerations of the judges of the Gorontalo Religious Court in the determination of Number. 77 / pdt.p / 2020 / PA. Gtlo. The author in his research uses normative research methods conducted by researching directly in cases that occur during society. Research is focused on describing legal issues, analyzing legal products, then presenting them systematically. The results of this study show that: 1) The legal position of the status of children born due to marriage under the hands in case Number. 77/Pdt.p/2020/PA. Gtlo, the panel of judges argued that the marriage of the petitioners was following the terms and pillars of marriage according to Islamic law, it's just that the marriage did not meet the administrative requirements as desired by article 2 paragraph (2) of Law Number: 1 of 1974 jo Law No. 16 of 2019 on marriage, so that according to Islamic law the marriage is still considered valid. Thus causing legal consequences, such as the rights and obligations of the husband and wife, marital property, the relationship between both parents and children (nasab), obligations of child maintenance (hadhanah), and inheritance. (2) Legal considerations used by the judges of the Gorontalo Religious Court in determining the petitioners' application in this case number 77 / Pdt.P / 2020 / PA. Gtlo there are at least three references of judges, namely, the evidence submitted by the applicants, the testimony of witnesses, and the provisions of the law (law) relating to the silverware.